STRATEGI GURU UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA DIKELAS V SD NEGERI PASIR GADUNG I - Wiranda Salsabila Cahyani putri; Mujazi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to find out and describe teacher strategies and student challenges in mathematics learning in class V. The research method used is descriptive qualitative. The data collection techniques used were observation, interviews and documentation. The research results obtained in teacher strategies for increasing motivation in learning mathematics in class V are: (1) Ensuring the availability of mathematics learning facilities. (2) Consistency in implementing mathematics learning strategies. (3) There is a special approach in learning mathematics. (4) Active involvement of students in mathematics learning. (5) Creating interesting learning in mathematics learning (6) Applying the storytelling method in mathematics learning. (7) There is a record of grades in mathematics learning in class. And there are 2 challenges for students in learning mathematics in class V as follows: (1) Lack of student interest in learning mathematics. (9) There are internal and external factors in the mathematics learning process at school.